Moro heroes in Philippine history textbooks: the marginalization of the historical narratives of Muslim Filipino heroes in social studies education - Mejorada, Alvin G.
Through an analysis of contemporary Philippine history textbooks used in teaching the subject of social studies, this study explored the representation and portrayal of Moro heroes and their historical narratives. While the presence of Muslim Filipinos and their heroes were evident in the textbooks studied; such representation paled in comparison with the number of pages, words, name mentions, and illustrations utilized in the discussion of their Christian Filipino counterparts. Generally, the textbooks analyzed portrayed the narratives of Muslim Filipinos in a manner which glorified their experiences and struggles, but there were still sentences and paragraphs published in these learning materials that caused the perpetuation of misconceptions and stereotypes about Muslim Filipinos that furthered the Orientalist perspective that was inherited from our colonial experience. This research argues that the underrepresentation and misrepresentation of Muslim Filipinos in current learning materials continues to produce feelings of othering and alienation on the part of Muslim Filipino students and may have been influenced by certain factors - such as the scarcity of reference materials on the history of Muslim Filipinos, the limitation of the educational experience of authors and publishers, and the commercial pressures of the privatized textbook publishing industry. While this study recognizes that there is a certain level of counter-hegemonic resistance that has already begun to take shape in our educational system, the larger problem of the construction of national identity that is deemed to disregard the cultural pluralism of society still needs to be addressed.